Anxiety, locus of control and sociodemographic factors associated with adherence to an annual clinical skin monitoring: a cross-sectional survey among 1000 high-risk French patients involved in a pilot-targeted screening programme for melanoma. Issue 10 (5th October 2017) - Rat, Cédric; Hild, Sandrine; Gaultier, Aurelie; Khammari, Amir; Bonnaud-Antignac, Angelique; Quereux, Gaelle; Dreno, Brigitte; Nguyen, Jean Michel
Abstract : Objective: The aim of the study was to assess whether adherence to annual clinical skin monitoring is dependent on patient sociodemographic characteristics or personality traits. Design: The study was a questionnaire survey. Setting and participants: Data were collected between February and April 2013 in a sample of 1000 patients at high risk of melanoma who participated in a pilot-targeted screening programme in western France. Outcome measures: Sociodemographic data, overall anxiety level (State-Trait Anxiety Inventory questionnaire), locus of control (Multidimensional Health Locus of Control scale) and levels of anxiety specifically associated with screening and melanoma were collected. Actual participation in the skin monitoring examination was reported by 78 general practitioner investigators. Statistical analysis: Statistical analysis was performed using R statistical software. Factors associated with non-adherence were identified by multivariate analysis. Results: Our analysis included 687 responses (526 adherent patients and 161 non-adherent patients). Non-adherence was higher in younger patients and in men (OR=0.63 (0.41–0.99)). Viewing health status as dependent on external persons (OR=0.90, 95% CI 0.83 to 0.97) or determined by chance (OR=0.89, 95% CI 0.80 to 0.98) and overall anxiety (OR=0.98, 95% CI 0.97 to 0.99) were also factors associated with non-adherence. In contrast, there was no link between anxiety specifically associated with the screening performed or melanoma and patient adherence to monitoring. Adherence was higher in married patients (OR=1.68 95% CI 1.08 to 2.60). Conclusions: The results of this study suggest that sociodemographic and psychological characteristics should be considered when including patients at elevated risk of melanoma in a targeted screening programme. Trial registration number: NCT01610531; Post-results.